Kanchan arsenic filter: evaluation and applicability to Cambodia - Davin Uy; Tommy K. Ngai; Tom Mahin; C. Samnang; M. Saray; M. Adam; D. Baker (2009)
Arsenic contamination of drinking water in rural Cambodia has driven the search for mitigation options. The Kanchan Arsenic Filter for household water treatment is being evaluated for its applicability as one potential solution to this crisis. In 2008, ten Kanchan filters, in 5 configurations, were tested over a 30 week period. Each filter treated 40 L/day. The ground water had arsenic and phosphate concentrations averaging 637 μg/L and 5.09 mg/L respectively, representing challenging source water. Arsenic removal averaged 9597% for all configurations. After the first week of start up, all but 1 in 224 samples achieved the Cambodian standard of 50 μg/L. Arsenic removal was not significantly affected by the flow rate or the cleaning of the filter. There was no apparent depletion of arsenic adsorption capacity over the 30 weeks (8400 L filtered). Iron and turbidity removals were also very high, improving the user acceptability of this technology.